A comparative study of different optimised mirrors layouts of Linear Fresnel concentrators on annual energy and exergy efficiencies. Issue 1 (31st December 2022) - Roostaee, Amin; Ameri, Mehran
Abstract : This paper is aimed at investigating optimised mirror layout effects of Linear Fresnel Concentrators (LFC) by evaluating the annual energy and exergy efficiencies. Subsequently, a north–south central receiver LFC with cylindrical mirror profile and Trapezoidal Cavity Receiver (TCR) were considered. Two distinct mirrors reference configurations such as the sun and specific references and four different layouts such as the constant width and shift, constant width and variable shift, variable width and constant shift and variable width and variable shift studied separately and for each of them, the widths and shifts of mirrors optimised through an analytic method. A TCR was designed for every layout, and its heat loss was estimated from numerical modelling to derive the annual energy and exergy values. It was concluded that considered mirrors reference configurations and mirrors layouts play an important role in energy and exergy efficiencies. Furthermore, variable width layouts have a higher impact on energy and exergy amounts than variable shift layouts due to their effects on the receiver dimension and its heat loss. Finally, besides the highest efficiency of variable width and shift layout in specific reference, the constant and variable width layouts demonstrate superior performance in sun and specific references, respectively.